2009
DOI: 10.1097/ccm.0b013e318194b1bf
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression associated with interleukin-1R-associated-kinase-M upregulation predicts mortality in Gram-negative sepsis (melioidosis)

Abstract: Immunosuppression in sepsis caused by B. pseudomallei is associated with an upregulation of IRAK-M and an indicator of poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 51 publications
6
61
0
Order By: Relevance
“…In contrast, lung macrophages obtained from IRAK-M -/-mice with sepsis released more TNF-α upon exposure to P. aeruginosa, which was associated with a markedly improved host defense against this nosocomial pathogen (9). As such, this previous study expanded knowledge on the role of IRAK-M in the immune suppression associated with sepsis (6)(7)(8)33). Thus far, the involvement of IRAK-M in the innate immune response to primary bacterial pneumonia in the previously healthy host remained unexplored.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, lung macrophages obtained from IRAK-M -/-mice with sepsis released more TNF-α upon exposure to P. aeruginosa, which was associated with a markedly improved host defense against this nosocomial pathogen (9). As such, this previous study expanded knowledge on the role of IRAK-M in the immune suppression associated with sepsis (6)(7)(8)33). Thus far, the involvement of IRAK-M in the innate immune response to primary bacterial pneumonia in the previously healthy host remained unexplored.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, enhanced IRAK-M expression has been implicated in the immune suppression frequently observed in patients with sepsis, a condition also called LPS tolerance and characterized by a reduced capacity of immune cells to release proinflammatory cyto kines upon restimulation. Indeed, IRAK-M -/-cells did not become as tolerant to LPS upon reexposure to this bacterial component as WT cells (6), whereas our laboratory recently reported that LPS tolerance observed in healthy humans exposed to intravenous LPS and in patients with gram-negative sepsis correlated with enhanced IRAK-M expression in circulating leukocytes (7,8). Most importantly, in mice with polymicrobial abdominal sepsis, enhanced IRAK-M expression in pulmonary macrophages contributed to a diminished capacity of these cells to respond to Pseudomonas aeruginosa ex vivo, which resulted in a strongly impaired host defense response during secondary (following abdominal sepsis) Pseudomonas pneumonia (9).…”
Section: Introductionmentioning
confidence: 86%
“…The induction of LPS tolerance during these clinical conditions may in the short term be beneficial by preventing excessive inflammation, but in the longer term be deleterious by hampering an adequate defense response to opportunistic infections. Despite the difference in kinetics, recent data indicate that early transient and classical LPS tolerance may be regulated through similar mechanisms (10,15).…”
mentioning
confidence: 99%
“…LPS injection. Early transient LPS tolerance differs in its kinetics from classical LPS (or endotoxin) tolerance, observed in experimental animals (6) and leukocytes of patients with sepsis (7)(8)(9)(10), systemic inflammatory response syndrome (11), major surgery (12), and trauma (13,14), which lasts for several days to weeks. The induction of LPS tolerance during these clinical conditions may in the short term be beneficial by preventing excessive inflammation, but in the longer term be deleterious by hampering an adequate defense response to opportunistic infections.…”
mentioning
confidence: 99%
“…Studies on infection of phagocytic cells have mainly utilized mouse cell lines, although recently there have been a number of studies concerning the immune response of human patients, in particular the involvement of cytokines in sepsis (Wiersinga et al, 2009(Wiersinga et al, , 2010. Since the outcome of infection is known to be dependent on the human immune response it is possible that B. pseudomallei strains may abrogate the immune response.…”
Section: Discussionmentioning
confidence: 99%